La elección de objeto y el goce de los padres (2004)
ABSTRACT: This paperis the result ofthe work carried out in the conference “Freud 100 years later”, University of Antioquia, 2015. It presents a reflection on the text Instincts and Their Vicissitudes from 1915 and on literature as a resource, particularly Leopold Von SacherMasoch’s work. Thus, a discussion and comprehension link is established between the theory of the drives, the notion of masochism, and their place in the constitution of neurosis